RiPCA: An Assay for the Detection of RNA‐Protein Interactions in Live Cells. Issue 2 (3rd February 2022) - Rosenblum, Sydney L.; Garner, Amanda L.
Abstract: Increasing interest in studying and modulating the interactions between RNAs and their RNA‐binding proteins has indicated the need for enabling technologies. Existing means of detecting RNA‐protein interactions (RPIs) are often limited to biochemical or post‐lysis methods or cell‐based methods that require the addition of an RNA‐based affinity tag, such as the MS2 hairpin, precluding them from use in detecting small or highly processed RNAs. Taking advantage of bioorthogonal chemistry‐ and split‐luciferase‐based technologies, we developed an assay for the detection of RPIs in live cells. This article details the protocol and design considerations for RiPCA, or R NA i nteraction with P rotein‐mediated C omplementation A ssay. © 2022 Wiley Periodicals LLC.